O uso de tecnologias digitais de informação e comunicação por professores da sala de recursos multifuncionais durante o período de pandemia - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
This research investigated how teachers acting in the Multifunctional Resource Room (MRS) worked in the year 2021 in the city of Ponta Grossa regarding the development of emergency remote teaching for Especial Education target students during the pandemic caused by the COVID-19 virus. The overall objective of this research was to analyze issues related to the use of Digital Information and Communication Technologies (DICT) by MRS teachers and their impact on the teaching and learning process in Special Education. The study was developed through a qualitative, exploratory research approach, also involving a bibliographical study and monographic method or case study contributions. The research subjects were selected using as a criterion, that they had worked in the MRS during the pandemic with the development of emergency remote teaching. The data obtained were collected through an electronic questionnaire made available through a WhatsApp access link consisting of twenty-five (25) questions, of which thirteen (13) were open and were analyzed according to the clipping of the recurrent themes with higher frequency. The responses obtained were analyzed and organized into categories considering the guided phases by Content Analysis, divided into preanalysis, material exploration, treatment of results, inference and interpretation. The main difficulties identified within the work of these teachers are related to the lack of knowledge in the area of technologies and the lack of skills for their use. It is considered that, in the face of such difficulties, the teacher has acted in a limited and immediate way. In this perspective, an educational product was developed in the format of an E-book, to serve as a guide for teachers working in Special Education. In the face of such difficulties, teachers’ actions were limited and immediatist. In this perspective, an educational product was developed in the format of an E-book, to serve as a guide for teachers working in Special Education. Thus, it is believed that it is important to periodically offer continuing education processes aimed at the use of technologies and provide moments of reflection that can collaborate with a greater understanding on the part of the teacher in relation to his/her role in the school.
Keywords: Ensino remoto emergencial; Educação Especial; Sala de Recursos; Multifuncionais; Tecnologias Digitais de Informação e Comunicação.; Emergency remote teaching; Special education; Multifunctional Resource; Room. Digital Information and Communication Technologies; CNPQ::CIENCIAS HUMANAS